2008
DOI: 10.5194/acp-8-1249-2008
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment of fine organic aerosol in Mexico City during the MILAGRO experiment 2006

Abstract: Abstract. Organic carbon (OC) comprises a large fraction of fine particulate matter (PM 2.5 ) in Mexico City. Daily and select 12-h PM 2.5 samples were collected in urban and peripheral sites in Mexico City from 17-30 March 2006. Samples were analyzed for OC and elemental carbon (EC) using thermal-optical filter-based methods. Real-time watersoluble organic carbon (WSOC) was collected at the peripheral site. Organic compounds, particularly molecular markers, were quantified by soxhlet extraction with methanol … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
138
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 222 publications
(160 citation statements)
references
References 40 publications
22
138
0
Order By: Relevance
“…Single scattering albedos in the MCMA and downwind are substantially lower than in other areas (such as the eastern United States) (Doran et al, 2007(Doran et al, , 2008Kleinman et al, 2008;Marley et al, 2009a;ParedesMiranda et al, 2009;Thornhill et al, 2008). These results are consistent with the significant amounts of black carbon and light-absorbing PAH coatings observed during these studies as well as during MCMA-2003Stone et al, 2008;Querol et al, 2008). Carbon-14 and stable carbon-13 measurements also have indicated that a major fraction of the total carbonaceous aerosol is coming from recent carbon sources including biomass and agricultural burning activities (Marley et al, 2009a;Aiken et al, 2010).…”
Section: Aerosol Optical Properties and Radiative Influencessupporting
confidence: 81%
“…Single scattering albedos in the MCMA and downwind are substantially lower than in other areas (such as the eastern United States) (Doran et al, 2007(Doran et al, , 2008Kleinman et al, 2008;Marley et al, 2009a;ParedesMiranda et al, 2009;Thornhill et al, 2008). These results are consistent with the significant amounts of black carbon and light-absorbing PAH coatings observed during these studies as well as during MCMA-2003Stone et al, 2008;Querol et al, 2008). Carbon-14 and stable carbon-13 measurements also have indicated that a major fraction of the total carbonaceous aerosol is coming from recent carbon sources including biomass and agricultural burning activities (Marley et al, 2009a;Aiken et al, 2010).…”
Section: Aerosol Optical Properties and Radiative Influencessupporting
confidence: 81%
“…The substrates were then analyzed by gas chromatography mass spectrometry (GC-MS) method (GC-6980, quadruple MS-5973, Agilent Technologies). Further details regarding this analytical method can be found in Stone et al (2008). In addition to the particle phase measurements, gas-phase aldehydes were also collected on silica vials activated with DNPH and analyzed according to the EPA method TO-11A -1999 (method TO-11A;US-EPA 1999).…”
Section: Time Integrated Chemical Analysesmentioning
confidence: 99%
“…The relatively low carbonyl content found in 20 Chamonix OA compared to the high carbonyl functionalisation rates measured for the photooxidation experiments (6 to 11%) supports the assumption that the Chamonix winter OA is mainly of primary origin, considering the abundance of carbonyl as a marker for SOA. In a recent study conduced at Mexico City, FTIR functional groups analyses have pointed out low functionalisation rates for carbonyls (0 to 1.5%) ) whereas SOA, mainly from biogenic origin, was a major fraction of OA (Stone et al, 2008;Hodzic et al, 2009). This result suggests that carbonyl abundance can not be considered as an univocal marker of SOA.…”
Section: Chamonix Urban Background Aerosolmentioning
confidence: 99%